UJI HIPOTESIS “JALAN-ACAK” DALAM FUNGSI KONSUMSI DI INDONESIA - Munawar Ismail; David Kalirge; Martanti Wahyurina (Journal of Indonesian Economy and Business (JIEB), 2005)
This study is aimed at testing the random-walk hypothesis in the Indonesian economyconsumption function. If the random-walk exists then the consumption can not be predictedsistematicaly. The study found that there was no random-walk in the Indonesianconsumption function either under the assumption of constant interest rate or that ofvariable interest rate. Other finding is that both nominal interest rate and the rate ofinflation had significant effect on the consumption.Keywords: consumption, random-walk, rational expectation, life cycle-permanent income